Studies on digestive enzymes in fish: Characterization and practical applications - Alarcón F.J.; Díaz M.; Moyano F.J. (Feeding tomorrow's fish, 1997)
Due to the special features of the aquatic environment, fish nutritionists are well aware of the difficulties and errors obtained when determinations of digestibility are carried out in vivo. Nevertheless, digestibility measurements for different feed ingredients, especially in the case of proteins, remain the nucleus of most of the experiments aiming at evaluating raw materials. At present, digestibility trials performed in vivo may be complemented, and in some cases preceded or substituted, by several biochemical techniques offering a wide range of practical applications. A three-step approach is proposed as a suitable means to obtain valuable results. Such an approach begins with the appraisal of specific activities of selected digestive enzymes, followed by the characterisation of such activities, and finally by the utilisation of all this information in order to simulate in vitro the digestive process taking place in fish or in aquatic organisms.
Workshop of the CIHEAM Network on Technology of Aquaculture in the Mediterranean (TECAM), 1996/06/24-26, Mazarrón (Spain)